Analysis Of The Influence Of Inflation, Money Supply, And Exchange Rate On Economic Growth In Indonesia - Hotsawadi Hotsawadi; Nuzulia Nuzulia (AKSES: Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of inflation, money supply, and the exchange rate on economic growth in Indonesia in the short and long term, covering the period 1982–2024. The analysis methods used are Vector Autoregression (VAR) and Vector Error Correction Model (VECM) to capture the dynamic relationship and long-term balance between macroeconomic variables. The results show that in the short term, inflation, money supply, and exchange rates do not have a significant effect on economic growth, which indicates a delay (time lag) in the transmission mechanism of economic policy. However, in the long term, the variables are cointegrated, indicating that macroeconomic variables tend to move towards equilibrium. Partially, exchange rates and inflation have proven to have a significant effect on long-term economic growth, with exchange rate depreciation driving export competitiveness, while controlled inflation increases aggregate demand. On the other hand, the money supply had a relatively limited influence, indicating that the transmission of monetary policy to the real sector was suboptimal. These findings affirm the importance of inflation and exchange rate stability as the main determinants of economic growth in Indonesia. Therefore, a coordinated monetary and fiscal policy framework is needed to maintain macroeconomic stability and promote sustainable economic growth.